Plexin-B1 silencing inhibits ovarian cancer cell migration and invasion - Zhang Yiqun; You Lanying; Chen Yin; Ji Li; Jiang Xuefeng; Zhou Li; Wang Yongjun; Wei Juncheng; Wu Mingfu; Zhou Ting; Hao Xing; Ye Shuangmei; et al. (BMC Cancer, 2010)
Abstract Background Elevated Plexin-B1 expression has been found in diverse human cancers and in non-neoplastic tissues, and it mediates diverse biological and pathological activities. However, whether or not Plexin-B1 expression is involved in human ovarian tumors remains unclear. In the present study, Plexin-B1 expression was explored in benign and malignant human ovarian tumor tissues. In addition, the impact of Plexin-B1 expression on ovarian cancer cell proliferation, migration and invasion were investigated in vitro. Methods Plexin-B1 expression was analyzed in normal and benign ovarian tissues and serous ovarian tumors (both borderline and malignant) by immunohistochemical staining, as well as in four human ovarian cancer cell lines (A2780, C13*, SKOV3, and OV2008) by RT-PCR and western blot analyses. Furthermore, endogenous Plexin-B1 expression was suppressed by Plexin-B1 siRNA in SKOV3 cells, which overexpress Plexin-B1. Protein levels of Plexin-B1, AKT and AKTSer473 were examined by western blot analysis. Cell proliferation, migration and invasion were measured with MTT, wound healing and boyden chamber assays, respectively, and the cytoskeleton was monitored via F-actin staining. Results Expression levels of Plexin-B1 protein were significantly higher in serous ovarian carcinomas than in normal ovaries or benign ovarian neoplasms, and in the former, Plexin-B1 expression was positively correlated with lymphatic metastasis, and the membrane and cytoplasm of cancer cells stained positively. SKOV3 cells displayed the highest Plexin-B1 expression at both the mRNA and protein levels among the four tested human ovarian cancer cell lines and was selected as a cell model for further in vitro experiments. Plexin-B1 siRNA significantly suppressed phosphorylation of AKT at Ser473 in SKOV3 cells, but it did not alter total AKT expression. In addition, silencing of Plexin-B1 in SKOV3 cells inhibited cell migration and invasion and reorganized the cytoskeleton, whereas cell proliferation was not affected. Conclusion Plexin-B1 expression correlates with malignant phenotypes of serous ovarian tumors, probably via phosphorylation of AKT at Ser473, suggesting that Plexin-B1 might be a useful biomarker and/or a novel therapeutic target.